Uji Kandungan fitokimia dan Etnobotani Tumbuhan Obat Tradisional Berbasis Pengetahuan Lokal di Kecematan Lambitu Kabupaten Bima - Nikman Azmin; Anita Rahmawati; Muhammad Eka Hidayatullah (UNIVERSITAS PGRI MADIUN, 2019)
This study aims to study the collection and use of traditional plants by the Bima community. The method used is in-depth interviews, field surveys and questionnaire techniques. Maseration and phytochemical screening tests were carried out to determine the content of active compounds in traditional plants. The results of this study indicate that the types of traditional medicinal plants used as phytochemical test samples consist of 19 types of traditional medicinal plants. Parts of medicinal plants used as raw materials that have medicinal properties in the form of leaves 40%, rhizomes 28%, Fruit 12%, stem 8%, roots%, sap or lenders 4%. Phytochemical test results show that the compounds contained in medicinal plants are Flavonoids, Alkaloids, Steroids, Terpenoids, Saponins and Tanins. Generally Bima people manage and utilize various types of medicinal plants, such as trees, shrubs, herbs and weeds as ingredients (herbs) in the treatment of various diseases